Improving the Quality of Honey and Socialitzion of Flora Nectar Producer as Bee Feed in the Bangunkarya Village Langkaplancar District Pangandaran - Winantris Winantris; Lia Jurnaliah (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Honey production depends on the availability of nectar and pollen as bee food. In Bangunkarya Village, this potential is abundant and has not been utilized optimally, which includes yards, gardens, and forest flora. At least fifteen residents have coffee plantations that have started to bear fruit and harvest; these people's coffee plantations are an essential source of nectar and pollen. Currently, only two residents are active in the honey business. The village in Langkaplancar District is currently active in becoming a Tourism Village in support of the Aspiring Geopark Pangandaran. Increasing the quality and production of honey is targeted in community service activities to contribute to advancing geo products. Activities include identifying nectar and pollen-producing flora, socializing nectar-producing flora, educating about hygienic honey products, and making attractive honey packaging. Two types of honey that have been improved in quality and given names to marketers are the name Hani Kuya, given to natural honey from Apis dorsata bees, and Rosisdin Honey for livestock honey from Teuwul bees (Heterotrigona sp.). Quality improvements include improving packaging, filtering techniques, dosage, and providing product name labels. Honey products that have experienced improvements in quality have been exhibited in Forum Group Discussion (FGD) activities at the Pangandaran Tourism office as a promotional step to encourage increased sales and economic value.